2004
DOI: 10.1128/iai.72.7.4309-4313.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Native or Recombinant Streptococcus pneumoniae Neuraminidase Affords Protection in the Chinchilla Otitis Media Model

Abstract: Streptococcus pneumoniae neuraminidase has been implicated as a virulence factor in the pathogenesis of pneumococcal otitis media. In this study, native neuraminidase was partially purified from cultures of S. pneumoniae by serial chromatography with DEAE-Sepharose and Sephacryl S-200. Recombinant neuraminidase, a 3,038-bp fragment of the neuraminidase A (nanA) gene, was cloned into the pET-28b vector and then expressed at high levels in Escherichia coli. Chinchillas were immunized subcutaneously with either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 30 publications
0
34
0
1
Order By: Relevance
“…In contrast, the nanA knockout is not attenuated in an intraperitoneal infection model (Berry & Paton, 2000). The importance of NanA for colonization has been underlined by its ability to afford protection against nasopharyngeal colonization and otitis media in chinchilla models (Long et al, 2004). Recently, two reports have demonstrated the precise function of NanA during pneumococcal colonization and pathogenesis.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…In contrast, the nanA knockout is not attenuated in an intraperitoneal infection model (Berry & Paton, 2000). The importance of NanA for colonization has been underlined by its ability to afford protection against nasopharyngeal colonization and otitis media in chinchilla models (Long et al, 2004). Recently, two reports have demonstrated the precise function of NanA during pneumococcal colonization and pathogenesis.…”
Section: Biological Activities Of Unusually Cell-wallanchored Cholinementioning
confidence: 99%
“…Pneumococcal neuraminidase activity also provides a source of carbohydrates for bacterial metabolism, cleaving sugars from the mucosal surface (8,23,61), but whether this significantly contributes to bacterial growth in vivo has not been clearly established. Several studies have suggested that nanA mutants colonize the rodent respiratory tract less efficiently than wild-type strains (31,40,52), and vaccination with purified NanA affords some protection against nasopharyngeal colonization and otitis media (29,30,53). However, the differences can be mouse strain and animal model dependent (6,13,22,23).…”
mentioning
confidence: 99%
“…In patients with pneumococcal infection, a direct correlation exists between levels of N-acetylneuraminic acid in cerebrospinal fluid and development of coma and adverse outcome (31). Recently, immunization with NanA has also been demonstrated to afford protection against nasopharyngeal colonization and experimental otitis media (27).…”
mentioning
confidence: 99%